Analisis Kemampuan Komunikasi Matematis Berdasarkan Teori Vygotsky dalam Menyelesaikan Soal Cerita Open Ended Siswa SD - Aliya Dwi Juniyanti; Prischa Lely Dwi Cahyati; Fradiska Putri Triswahyuni; Anggita Neswa Virdaniya; Pinasthi Dwi Mustiko; Rissa Prima Kurniawati (Prosiding Konferensi Ilmiah Dasar, 2026)
This study aims to describe the mathematical communication skills of fifth-grade elementary school students in solving open-ended story problems based on Vygotsky’s theory. This research employed a descriptive qualitative approach with five fifth-grade students of SD Negeri Puhti 2 selected through purposive sampling. Data were collected through written tests and documentation of students’ work. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that students’ mathematical communication skills were demonstrated through their ability to express mathematical ideas, explain solution steps, use mathematical symbols, present representations, and communicate conclusions. Although some students still experienced calculation errors, students were generally able to communicate mathematical ideas in solving open-ended problems.